PEMBERDAYAAN SEKTOR INFORMALDALAM UPAYA PENINGKATAN PENDAPATAN MASYARAKAT - Amir Dedoe,M.Si, Drs. (Universitas Bangka Belitung, 2013)
This Â research Â aims Â to Â explain Â wheater Â government Â intervention Â in Â the Â form Â of capitalization, Â education, Â training/skill, Â and Â organization Â estabilishment Â could Â form ators of Â informal Â sector Â in Â increasing Â their Â income, Â and Â analyze Â the Â impact Â of government intervention on the increase of community income of informal sector. This research was a case study used a descriptive-qualitative analysis. The data were obtained through observation and in depth interview. The sample was selected using purposive sampling method. Since the actors of informal sector working as sidewalk traders Â were Â divided Â into Â certain Â groups, Â the Â key Â informant Â were Â also Â selected purposively. These groups were the sidewalk traders who were not married and that been Â working Â for Â less Â than Â five Â years Â and Â the Â ones Â who Â were Â maried Â and Â had Â been working Â for Â more Â than Â five Â years. Â The Â data Â were Â than Â processed Â using Â qualitative analysis.The Â results Â show Â that Â the Â participation Â of Â informant Â in Â informal Â sector Â activity Â as sidewalk traders in Sungailiat village is caused by their familyâs economic condition. The factors affecting the business of sidewalk trades are economic need and limited capital. The Â prospect Â of Â business Â development Â of Â sidewalk Â traders Â indicates Â a positive trend by obtaining capital aid from the local government of Bangka Regency accompanied Â by Â forming Â institution. Â By Â such Â and Â aid, Â the Â sidewalk Â traders Â could increase their business volume and develop it by making use of the strengthening of existing institution.keyword : Empowerment and informal sector